Accounting Software Selection Criteria for International Companies and User Satisfaction - Enikő LŐRINCZOVÁ; Tomáš RAIN; Aydin MALDAN (Communications of International Proceedings, 2021)
The fundamental accounting software selection criteria are related to content, technical criteria and user-friendliness. International companies with subsidiaries all over the world need more functions, such as multi-currency support, multi-language options, options for local taxation, but also the ability to work remotely and a cloud-based system. The aim of the paper is to point out the criteria which are important for chosing an international accounting software and to evaluate the user satisfaction with three software – Microsoft Dynamics GP, Oracle Netsuite and SAP Business One – used in international companies, based on a questionnaire survey.
Keywords: Accounting software selection criteria; cloud accounting; international features of accounting softwares; multicurrency; ERP